Examination of the newborn - Gruszfeld, Dariusz (Przewodnik Lekarza/Guide for GPs, 2008)
One needs to take into consideration the most frequent problems of neonatal period during examination of the newborn. It is possible to find congenital defects, metabolic or genetic syndromes, as well as prematurity related problems. It is necessary to pay particular attention to neurological examination because of possible consequences and necessity of careful follow up.